Evaluation of the Mechanical Properties of Polypropylene and Coir Fiber Composites: Contributions to the Circular Economy - Guilherme de Oliveira Martins; Silvia Angélica Domingues de Carvalho; Karine Cappuccio de Castro; Ivana Cesarino; Alcides Lopes Leão (Journal of Natural Fibers)
Materials developments has been constantly updated, observing the competitiveness for low cost, easy production and sustainability, the need arises to produce efficient, viable products that generate less environmental impact. Biobased composites can replace conventional materials, and those made using in natural fibers is a growing worldwide alternative. Coir fiber is a value-added material with satisfactory and superior mechanical properties compared to other natural fibers, in addition to its high availability. The aim of this study was to evaluate the mechanical properties of polypropylene and coir fiber composites and of sheets made with coir fiber alone, without the addition of binders. Composites with 20% and 40% fiber and different particle sizes were evaluated using tensile, flexural, hardness and impact resistance tests. The flexural modulus, water absorption and swelling of the sheets were evaluated. A correlation between the variables showed interdependence between fiber volume and melt flow index of 96%; breaking energy and moisture content showed a strong correlation of 83% and for the tensile, flexural and hardness tests, correlations of up to 94%. For the sheets, despite the limitation observed in relation to the pressure applied, the production process proved to be viable and with the possibility of improving their properties.